Training on utilization of planted containers from used goods in two of Primary Schools (SD model Al Azhar Medan and SD Namira Medan) in North of Sumatra - Haryati; Siregar, Ameilia Zuliyanti; Sitepu, Suzanna Fitriany; Jamilah; Lubis, Alida (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
With the holding of training on the use of used goods into a planting container for vegetable crops in the two schools (SD Model Al Azhar Medan and SD Namira), it is expected to foster creative and innovative work in science and technology capable of producing a system, design, model of goods in the form of pouring ideas or creative ideas which is original, visionary and implementative to find solutions to problems that are relevant to the environmental problems associated with agriculture. This training was carried out for 5 months (July-November 2019) through several stages, starting from problem identification, location initiation, training in the provision of used goods and vegetable cultivation. Then do the practice and guidance in the field, followed by information dissemination and publicity in mass media, making you tubes from the creation of used goods from these elementary school students. Through this training, there was an increase in the knowledge and understanding of students about the processing of used goods from bottles, wood, cans, plastics, shoes, pants, oil packaging that were converted into planting containers. Then the creations are placed as a corner of the school garden. Synergy of the University of Sumatera Utara in developing superior knowledge that is beneficial has the full support of the community, especially students of SD Model Al Azhar Medan and SD Namira Medan.